Pengaruh Bauran Pemasaran Pada Penjualan Cerutu PT BIN Di Indonesia - Musaiyadi (STIE Mandala Jember, 2020)
This paper aim to analyze how so far the effect of marketing mix toward total sale of BIN’s cigars in local market. By using mountly data from 2016.1 to 2018.12 on error correction model, this research finds out: (1) product varian of BIN’s cigars significant statistically influence total sale of BINs cigars in local market positively. (2) average price of BIN’s cigars statistically influences total sales of BIN’s cigars in local market negatively. (3) promotion costs of BIN’s cigars statistically did’nt influences total sales of BIN’s cigars in local market negatively. (4) distribution channels of BIN’s cigars statistically did’nt influences total sales of BIN’s cigars in local market negatively. (5) All of those independent variables significant statistically and simultaneously influences total sales of BIN’s cigars in local market positively.